Air cold plasmas as a new tool for nitrogen fixation in agriculture: underlying mechanisms and current experimental insights - Aceto, Domenico; Ambrico, Paolo F.; Esposito, Fabrizio (Frontiers in Physics, 2024)
Nitrogen fixation is crucial for plant growth and global agriculture, especially with the projected population growth requiring a significant increase in food production. Traditional nitrogen fixation relies on the Haber-Bosch (H-B) process, which is energy-intensive and environmentally harmful due to greenhouse gas emissions. Emerging technologies, such as cold plasma, offer promising alternatives with lower energy consumption. Cold plasma facilitates reactive nitrogen species generation under ambient conditions, potentially improving the production efficiency of nitrogen oxides (NOx). However, optimizing cold plasma nitrogen fixation requires a synergy between experimental and theoretical approaches. Accurate input data are essential for refining theoretical models, which can then guide the design of more efficient processes. This integrated approach can leverage renewable energy, operate on smaller scales, and minimize environmental impacts, making cold plasma a sustainable solution for future nitrogen fixation needs.